2012
DOI: 10.1111/j.1570-7458.2012.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and origin of Busseola fusca populations in Cameroon

Abstract: The cereal stem borer Busseola fusca Fuller (Lepidoptera: Noctuidae) is a species endemic to sub‐Saharan Africa. It is a major pest of maize and cultivated sorghum, the main cereal crops on the African mainland. Previous studies using mitochondrial markers revealed the presence of three clades of haplotypes (W, KI, KII) among B. fusca populations. Previous preliminary studies based on a few B. fusca individuals collected from three localities within the Guineo‐Congolian rain forest in Cameroon demonstrated a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
(50 reference statements)
3
8
0
Order By: Relevance
“…The observed differences in physiological adaptation suggest that S. calamistis and B. fusca are composed of several ecologically differentiated populations. Such ecologically differentiated populations are in agreement with recent results on B. fusca and S. calamistis reporting genetic differentiation of populations (Sezonlin et al, , ; Ong'amo et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…The observed differences in physiological adaptation suggest that S. calamistis and B. fusca are composed of several ecologically differentiated populations. Such ecologically differentiated populations are in agreement with recent results on B. fusca and S. calamistis reporting genetic differentiation of populations (Sezonlin et al, , ; Ong'amo et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…This result is similar to the one obtained in the Lepidoptera species "Plutella xylostella" [51]. For the same species, in Cameroon and China substantial genetic variation and high gene flow among regions have been reported [52,53]. However, recent studies also provide contrasting results and have reported genetic differentiation and isolated populations in Lepidoptera species such as for Boloria eunomia, Sesamia nonagriodes and Diatraea saccharalis [48,49,54].…”
Section: Discussionsupporting
confidence: 54%
“…In the noctuid Trichoplusia ni (H€ ubner), genetic analyses revealed long-distance dispersion from west to east among North American populations, but geographic areas with large greenhouse populations showed high isolation by distance, correlated with Bt resistance differentiation (Franklin et al 2010). Our results suggest that B. fusca is a good disperser: (i) the same microsatellite cluster is present from southern Africa to southern Cameroon, confirmed by the extension of East African mitochondrial clades in Cameroon (Sezonlin et al 2006(Sezonlin et al , 2012; (ii) apart from the east-west separation (0% introgression), the clusters exchanged migrants (9.0% introgression between the eastern and southern clusters). Locally, Btfree refuge strategy or the plantation of a certain area with non-Bt plants may help to delay the apparition of resistance.…”
Section: Circuit-sdm Model and The Management Of Bt Resistance In Inssupporting
confidence: 51%
“…Our results suggest that B. fusca is a good disperser: (i) the same microsatellite cluster is present from southern Africa to southern Cameroon, confirmed by the extension of East African mitochondrial clades in Cameroon (Sezonlin et al . , ); (ii) apart from the east–west separation (0% introgression), the clusters exchanged migrants (9.0% introgression between the eastern and southern clusters). Locally, Bt ‐free refuge strategy or the plantation of a certain area with non‐ Bt plants may help to delay the apparition of resistance.…”
Section: Discussionmentioning
confidence: 99%